2008
DOI: 10.1210/en.2008-0944
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet Delays and Fasting Advances the Circadian Expression of Adiponectin Signaling Components in Mouse Liver

Abstract: The circadian clock controls energy homeostasis by regulating circadian expression and/or activity of enzymes involved in metabolism. Disruption of circadian rhythms may lead to obesity and metabolic disorders. We tested whether the biological clock controls adiponectin signaling pathway in the liver and whether fasting and/or high-fat (HF) diet affects this control. Mice were fed low-fat or HF diet and fasted on the last day. The circadian expression of clock genes and components of adiponectin metabolic path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 49 publications
5
90
0
Order By: Relevance
“…However, recent studies have shown that introduction of a high-fat diet to animals leads to rapid changes in both the period of locomotor activity in constant darkness and to increased food intake during the normal rest period under light-dark conditions [178]. These changes in behavioral rhythmicity correlated with disrupted clock gene expression within hypothalamus, liver, and adipose tissue, and as well as with altered cycling of hormones and nuclear hormone receptors involved in fuel utilization, such as leptin, thyroid stimulating hormone (TSH), and testosterone in mice, rats, and humans [178][179][180][181][182][183]. Furthermore, a high-fat diet modulates carbohydrate metabolism by amplifying circadian variation in glucose tolerance and insulin sensitivity [119].…”
Section: Effect Of High-fat Diet On Circadian Rhythmsmentioning
confidence: 99%
“…However, recent studies have shown that introduction of a high-fat diet to animals leads to rapid changes in both the period of locomotor activity in constant darkness and to increased food intake during the normal rest period under light-dark conditions [178]. These changes in behavioral rhythmicity correlated with disrupted clock gene expression within hypothalamus, liver, and adipose tissue, and as well as with altered cycling of hormones and nuclear hormone receptors involved in fuel utilization, such as leptin, thyroid stimulating hormone (TSH), and testosterone in mice, rats, and humans [178][179][180][181][182][183]. Furthermore, a high-fat diet modulates carbohydrate metabolism by amplifying circadian variation in glucose tolerance and insulin sensitivity [119].…”
Section: Effect Of High-fat Diet On Circadian Rhythmsmentioning
confidence: 99%
“…By contrast, only a few studies have investigated the relationship existing between different diets and circadian clock regulation in wild-type mice. The effect of administering high-fat diet on the expression of clock genes has so far been studied in different tissues (Kohsaka et al 2007;Barnea et al 2009;Hsieh et al 2010;Yanagihara et al 2006), but to date, alterations of clock gene expression in the gut following administration of high-fat diet in wild-type mice have never been reported.…”
Section: Gene Expressionmentioning
confidence: 99%
“…35 Samples were run on an SDS-polyacrylamide gel (10% for AMPK and SIRT1, 7.5% for ACC) and subsequently proteins were transferred into a nitrocellulose membrane. Blots were incubated with mouse anti-AMPK/pAMPK/ACC/pACC (Cell Signaling Technology Inc., Danvers, MA, USA) or anti-SIRT1 (Millipore, Billerica, MA, USA) antibodies and after several washes with anti-rabbit IgG horseradish peroxidase-conjugated secondary antibody (Cell Signaling Technology Inc.).…”
Section: Western Blot Analysismentioning
confidence: 99%